Elevated methane alters dissolved organic matter composition in the Arctic Ocean cold seeps - Sert, Muhammed Fatih; Schweitzer, Hannah D.; de Groot, Tim R.; Kekäläinen, Timo; Jänis, Janne; Bernstein, Hans C.; Ferré, Bénédicte; Gründger, Friederike; Kalenitchenko, Dimitri; Niemann, Helge (Frontiers in Earth Science, 2023)
Cold seeps release methane (CH4) from the seafloor to the water column, which fuels microbially mediated aerobic methane oxidation (MOx). Methane-oxidising bacteria (MOB) utilise excess methane, and the MOB biomass serves as a carbon source in the food web. Yet, it remains unclear if and how MOx modifies the composition of dissolved organic matter (DOM) in cold seeps. We investigated MOx rates, DOM compositions and the microbial community during ex-situ incubations of seawater collected from a cold seep site at Norskebanken (north of the Svalbard archipelago) in the Arctic Ocean. Samples were incubated with and without methane amendments. Samples amended with methane (∼1 µM final concentration) showed elevated rates of MOx in both seep and non-seep incubations. Fourier transform ion cyclotron resonance mass spectrometry (FT-ICR MS) analyses showed that the number of DOM formulas (i.e., molecular diversity) increased by up to 39% in these incubations. In contrast, the number of formulas decreased by 20% in samples not amended with methane, both from non-seep and seep locations. DOM composition was thus altered towards a more diverse and heterogeneous composition along with elevated methanotrophic activity in methane-amended conditions. In addition to microbial DOM production, abating microbial diversity indicates that elevated DOM diversity was potentially related to grazing pressure on bacteria. The diversity of DOM constituents, therefore, likely increased with the variety of decaying cells contributing to DOM production. Furthermore, based on a principal coordinate analysis, we show that the final DOM composition of non-seep samples amended with methane became more resemblant to that of seep samples. This suggests that methane intrusions will affect water column DOM dynamics similarly, irrespective of the water column’s methane history.